Proses Pembelajaran PKn dalam Meningkatkan Kreativitas Peserta Didik melalui Pembelajaran Berbasis Masalah di SMAN 3 Probolinggo - Abdul Basit; Sapriya Sapriya (MODELING: Jurnal Program Studi PGMI, 2016)
Problems at this research is caused by a less optimal learning process Civics in SMAN 3 Probolinggo which implies the lack of development of citizens who are intelligent and good (smart and good citizen). The purposes of this study are to describe the implementation of PBM in enhancing the learners creativity. The research methodology used in this research is a qualitative approach with descriptive methods. The research subjects are including principals, teachers, and learners. In collecting the data, the techniques used observation, interviews, and documentation. Data were analyzed using data reduction, data presentation and conclusion/verification. The finding of this research revealed that implementation of PBM on the subjects of Civics in enhancing the creativity of learners are related with the learning steps, such as the introduction, the main activities and the closing activity. However, strategy of learning used less creative and almost of all materials are suitable Civics using PBM strategy. Therefore, in preparing PBM through the method of discussion or debate, teachers need to identify learning materials related with the mind map.